When Is the Averaging Effect Present in Auditor Judgments? - Lambert, Tamara A.; Peytcheva, Marietta (Contemporary Accounting Research, 2020)
ABSTRACT Auditing standards task auditors with collecting sufficient appropriate evidence to form audit judgments. Yet, cognitive psychology documents a robust finding in which people evaluate a bundle of relevant, directionally consistent evidence as though averaging the strength of the components. In consequence, a bundle of evidence may be viewed as weaker evidence than the bundle's strongest evidence item alone. We experimentally examine whether this averaging effect occurs in an audit context, and we test a potential moderator. In three independent mini‐cases, we ask auditor participants to make judgments about going concern, internal controls, and fraud risk. We present auditors with unfavorable audit evidence relevant to each judgment, manipulating whether we present a single strong evidence item or bundle it with a weaker evidence item. We also manipulate the auditor's initial impression of the client's state. We find that experienced auditors succumb to the averaging effect, making more strongly unfavorable judgments in response to the single evidence item than the bundle, and that this bias is reduced when the observed evidence is inconsistent with the auditor's initial impression. We interpret our results as consistent with the dual‐processing theory of cognition.